The long-term impact of matching and rebate subsidies when public goods are impure: Field experimental evidence from the carbon offsetting market - Martin Kesternich; Andreas Löschel; Daniel Römer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
In this paper, we investigate both short- and long-term impacts of financial stimuli on public goods provision when contributions are tied to individual harm-related behavior. We conduct a large-scaled field experiment to examine voluntary contributions to a carbon offsetting program during the online purchase of a bus ticket. We systematically vary the individual payoff structure by introducing different matching grants (1/3:1, 1:1, 3:1) and price rebates (r-25%, r-50%, r-75%). Our results show that price rebates are more effective than matching schemes in raising participation rates while matching grants induce higher contributions to the offsetting program. We suspect differences in the personal responsibility for the compensated emissions to drive this result. Analyzing repeated bookings, we find decreasing treatment effects for returning customers except for the case of 1:1 matching grants. The equal matching scheme is also the only intervention that increases net contributions of customers compared to the control group.
Keywords: H41; C93; D03; L92; 330; voluntary carbon offsets; randomized field experiment; public goods; rebate subsidy; matching subsidy